In Search of Quality Education: The E-Learning Implementation as the Impacts of the COVID-19 Pandemic - Ikeu Kania; Dini Turipanam Alamanda; Mila Karmila; Mutiana Budiman (Indonesian Research Journal in Education |IRJE|, 2022)
The appearance of the disease epidemic induced by Novel Coronavirus (COVID-19) leads to some changes in life aspects, including in the learning process in the Education unit, particularly in colleges. The e-learning model is one of the models implemented in Garut University to prevent coronavirus transmission. This research aimed to describe an e-learning activity conducted by Garut University during the pandemic. The research method used was survey to examine the positive and negative effects of online learning activities. The technique of collecting data used was an online questionnaire via WhatsApp with 181 students. The results showed that e-learning activity conducted by Garut University had not been conducted effectively for students, lecturers and the campus itself as e-learning system provider. Lecturer performance was the complained factor by students, but generally lecturing ineffectiveness was due to all academicians’ unpreparedness for dealing with the changes of learning system from face-to-face to online method.